The Role of Madrasah Principal Leadership in Achieving Student Learning Achievement - Marsiswandi, Marsiswandi; Mustari, Mohammad; Alqadri, Bagdawansyah (Jurnal Penelitian Medan Agama, 2025)
This study aims to reveal and analyze the role of the madrasah principal's leadership in improving student achievement at MAN 2 Mataram. The background of this study is based on the reality that amidst technological advances and easy access to information, student achievement is one of the important indicators in assessing the quality of educational institutions. The success of educational institutions in producing outstanding students cannot be separated from the strategic role of the madrasah principal as a leader who is able to manage resources, design superior programs, and create a conducive learning environment. The research method used is qualitative descriptive with data collection techniques through observation, in-depth interviews, and documentation. The informants in this study consisted of the madrasah principal, deputy head of student affairs, competition supervisors, and outstanding students. The results of the study show that the madrasah principal at MAN 2 Mataram has a very significant role in improving student achievement, both academic and non-academic. This role is realized through strategic planning, teacher empowerment, intensive coaching for students, and strengthening partnerships with various parties. The leadership strategy implemented focuses on a participatory and motivational approach, and is supported by a continuous evaluation system. The increase in the number of achievements over the past three years shows that effective leadership can have a real impact on student achievement. Thus, the leadership of the madrasah principal is a key factor in forming a superior and achievement-oriented school culture.